(untitled) (Journal of Material Science and Technology Research, 2022)
Abstract: Waste energy harvest using thermoelectric (TE) materials will be a potential solution to the serious environmental pollution and energy shortage problems. Due to limitations of current manufacturing techniques in geometry complexity and high density, TE devices are not widely utilized in daily life to gather waste energy. 3D printing brings an opportunity to solve the fabrication limitations. In this paper, a hybrid process was developed to fabricate thermoelectric materials by integrating hot pressing with stereolithography. The mold and punch were designed and printed to fabricate thermoelectric devices used on hot water tubes via stereolithography. The Sb2Te3 powders filled the 3D printed mold in a layered manner, and each layer of powders was compacted under the pressing of punch at a certain temperature and compressive force. The polymer mold was removed after the sintering process to form the final TE components. A series of experiments were conducted to identify the optimal heating temperature and compressive force. The microstructures morphology and electrical conductivity of fabricated Sb2Te3 samples were evaluated. This research work conducted a scientific investigation into the fabrication of TE material with a hybrid process, including hot pressing and 3D printing, to solve the current manufacturing challenges, providing perspectives on developments of TE devices used in various energy harvest applications.